STATIC BEHAVIOR ANALYSIS AT CYLINDRICAL SHELL STRUCTURES WITH FINITE ELEMENT METHOD - (NIM 25004065), Husnah
ABSTRACT: The Goal of this thesis is analyzing the static behavior of shell structure translational with cylindrical surface. The shell structure analysis refers to analytic method literature (exact method) Design and Construction of Concrete Shell Roof by G.S.Ramaswamy with case study: 1) short shell with hinge fixed, 2) short shell with end fixed, 3) long shell with hinge fixed, and 4) long shell with end fixed. Finite element method has been programmed and based on approach numerical method, that is cylindrical shell program for analyzing static behavior of shell and to make easier structure analysis solution. The result of analysis cylindrical shell program will be compared to analytic result (exact) and software SAP 2000 versions 9. Shell structure analysis process covers an identification phase of structure modeling, geometry input, encumbering, material parameter, then processed with calculation integration of gauss, orthogonal transformation operator, form function, Jacobian matrix, Jacobian matrix inverse, total rigidity of bending membrane shear. The output of static analysis and cylindrical shell program are stresses and displacements. The discussions analysis covers with boundary conditions, the relation of load and displacement, poissons ratio influence and structural thickness influence to behavior of static shell structure.